Membangun Aplikasi Media Pembelajaran “JALIBOARD” Berbasis Augmented Reality - Majid, Iqbal Abdul; Susanto, Fx. Guntur Putra; Fadlan, Nizar Izzuddin Yatim; Haryani, Prita (Faculty of Computer Science, University of Jember, 2024)
This research aims to build an Augmented Reality (AR) based